IDENTIFIKASI DAN SURVEY CALON PESERTA DIDIK TIDAK MAMPU DI KOTA MATARAM UNTUK REKOMENDASI BEASISWA PENDIDIKAN - L. Jatmiko Jati; Abdul Muhid; Maghfira Rizky Maulani; Putri Amalia Wardi; Apriani (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2023)
The aim of this community service is to reach prospective new students who have been previously identified to be recommended for assistance in the form of educational scholarships in the Mataram City area. This community service is a form of Bumigora University's commitment to advancing education in Indonesia by providing assistance to prospective students who are less well off financially. The service targets for prospective new students start from Jalan Cilinaya, Cakranegara District, Jalan Pejanggik, Selaparang District, Karang Bedil, Pagutan, Dasan Cermen Timur, and ends in Monjok. This service activity uses a qualitative approach with the Participatory Action Research (PAR) method with descriptive research type. The activity was carried out by visiting the home of each prospective student and then conducting a short interview with the prospective student's guardian. A total of 7 prospective students were visited by this service team. Based on wise and careful consideration, the results of this service implementation decided to recommend the seven prospective students who were surveyed based on the real conditions of the prospective students. Apart from being beneficial for the community, this service activity also really helps the campus in identifying prospective students who are less fortunate and worthy of being given assistance to obtain higher education.